Analysis of Public Service Efficiency (Sanitation Agencies) In South Sulawesi - Zaenudin - (Universitas Islam Indonesia, 2012)
The objective of this research is to know the relative efficiency of the sanitation service unit in each regency or municipality of South Sulawesi. The model for analysis is data envelopment analysis (DEA). The regions achieving efficiency for sanitation service during: (a) 2001 and 2002 were Makassar, Takalar and Maros, (b) for 2003 the region thatachieved efficient for sanitation service are Makassar, Pare-pare, Barru, Bone, Takalar, Maros and Pinrang (c) in 2005 the region that achieved efficiency in sanitation service were Makassar, Bone, Maros and Pare-Pare, (d) in 2006 the region that achieved efficiency for sanitation service were Makassar, Bone and Maros.Keyword: efficiency, sanitary public service agency